Protocol of REACH-01: a single-arm, open label, prospective study of HAIC sequential TAE combined with tislelizumab and surufatinib in unresectable intrahepatic cholangiocarcinoma - Li, Kang-shuai; Liu, Yi; Zhang, Tie-zhong; Xu, Yun-fei; Zhang, Zong-li (Frontiers in Pharmacology, 2024)
Introduction Gemcitabine and cisplatin remain the cornerstone for the treatment of advanced or unresectable biliary tract cancers, but the incidence rate of the grade 3 or 4 toxic effects is high (70.7%). In recent years, significant progress has been achieved in the systemic treatment of cholangiocarcinoma with immune checkpoint inhibitors (ICIs), targeted therapy, and hepatic artery infusion chemotherapy (HAIC). HAIC may elevate the local drug concentration in the liver to 10–100 times the drug plasma concentration; therefore, it may enhance tumor cytotoxicity while minimizing systemic adverse effects. HAIC combined with immunotherapy and targeted therapy resulted in acceptable tumor responses and tolerable toxic effects in the treatment of hepatocellular carcinoma (HCC). However, whether this combination strategy can benefit patients with unresectable intrahepatic cholangiocarcinoma remains unclear. Methods and Analysis We describe a single-arm, open label, prospective clinical trial of HAIC sequential transcatheter arterial embolization (TAE) combined with tislelizumab and surufatinib in patients with unresectable intrahepatic cholangiocarcinoma. TAE + HAIC was performed at an interval of at least 3 weeks, and oxaliplatin (85 mg/m2) and rituximab (3 mg/m2) were infused. TAE was performed using undrugged microspheres. Tislelizumab was infused every 3 weeks and surufatinib was administered orally once a day, with 3-5 capsules (50 mg/capsule) each time. We plan to enroll 28 participants in this study. The primary study endpoint was objective response rate (ORR). The secondary endpoints were progression-free survival (PFS), conversion to surgical resection rate, overall survival (OS), 1-year OS rate, disease control rate (DCR), quality of life (QoL), and incidence of adverse events. Trial registration number NCT06239532.